The Structure and Form of the French Enlightenment, Volume 1 : Esprit Philosophique - Wade, Ira Owen, 1896- (Princeton legacy library., 2015)
The author describes the influence on the Enlightenment of the intellectual currents that had been active in France, particularly the historical and humanistic esprit critique and the scientific esprit modern. In the first volume he traces the transformation they brought about in religion, ethics, aesthetics, science, politics, economics, and self-knowledge. His analysis of works by Voltaire, Diderot, and Rousseau--including the Encyclopedic--defines their organic unity and clarifies contradictions that appear to threaten the coherence, consistency, and logical continuity of the esprit philosophique.